2019
DOI: 10.7717/peerj.7055
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of bacterial E3 ubiquitin ligase effectors using reduced amino acid peptide fingerprinting

Abstract: Background Although pathogenic Gram-negative bacteria lack their own ubiquitination machinery, they have evolved or acquired virulence effectors that can manipulate the host ubiquitination process through structural and/or functional mimicry of host machinery. Many such effectors have been identified in a wide variety of bacterial pathogens that share little sequence similarity amongst themselves or with eukaryotic ubiquitin E3 ligases. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The E3 ubiquitin ligase is an enzyme with specific recognition of substrate proteins, and is significant part of the ubiquitination pathway ( 16 , 17 ). The E3 ubiquitin ligase is mainly divided into three types: HECT, TING, and u-box domain families ( 18 ). Among them, HERC4 belongs to the HECT family, and its gene is located on chromosome 10q21.3.…”
Section: Introductionmentioning
confidence: 99%
“…The E3 ubiquitin ligase is an enzyme with specific recognition of substrate proteins, and is significant part of the ubiquitination pathway ( 16 , 17 ). The E3 ubiquitin ligase is mainly divided into three types: HECT, TING, and u-box domain families ( 18 ). Among them, HERC4 belongs to the HECT family, and its gene is located on chromosome 10q21.3.…”
Section: Introductionmentioning
confidence: 99%
“…The desired recoding scheme (alphabet) and kmer length (k) are specified by the user. Six recoding alphabets are included ( Table 1 ) ( Arnold et al , 2009 ; Bacardit et al , 2009 ; McDermott et al , 2019 ; Yamada and Tomii, 2014 ), or the user may specify no recoding at all. Snekmer uses the specified alphabet and kmer length to calculate the potential kmer space of all possible kmer combinations.…”
Section: Resultsmentioning
confidence: 99%
“…At least one major annotation resource [Rapid Annotation using Subsystem Technology (RAST)] uses the kmer approach for protein annotation ( Edwards et al , 2012 ; Overbeek et al , 2014 ) and multiple newer tools, such as MMseqs2 ( Mirdita et al , 2019 ; Steinegger and Söding, 2017 ) and DIAMOND ( Buchfink et al , 2021 ) use kmers to increase the speed and sensitivity of searches in various ways. We previously extended the protein kmer approach via amino acid recoding (AAR), which uses chemical similarities between amino acids to simplify the sequence space ( McDermott et al , 2019 ). We found that a simple AAR grouping of amino acids by hydrophobicity or hydrophilicity performed well in classifying disparate families of ubiquitin ligase effector mimics from viral and bacterial pathogens ( McDermott et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AUC is defined as the area bounded by the receiver operating characteristic (ROC) curve and coordinate axis. The closer the AUC is to 1.0, the higher the authenticity of the detection method ( Bin et al, 2020 ; McDermott et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%